2012
DOI: 10.7860/jcdr/2012/4264.2550
|View full text |Cite
|
Sign up to set email alerts
|

Value of Indian Diabetes Risk Score among Medical Students and Its Correlation with Fasting Plasma Glucose, Blood Pressure and Lipid Profile

Abstract: Introduction: The Indian Diabetes Risk Score is a tool which was devised by the Madras Diabetes Research Foundation to screen people for the risk of developing Diabetes mellitus; it comprises of the family history, the abdominal circumference, age and the physical activity. Aim of the Study:This study was aimed at finding out whether the Indian Diabetes Risk Score (MDRF) correlated with the blood sugar levels, the lipid profile and the blood pressure readings of medical students.Methods: Seventy five female an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
4
12
0
Order By: Relevance
“…Of course many studies were done in India validating the IDRS score done by Anandh Vardhan et al among medical students, Lanord Stanley JM et al study among rural community in Tamil Nadu, Adhikari P et al among South Indian population. [7][8][9] All these validation studies accepts that the MDRF -IDRS predicts diabetes but also identified those with metabolic syndrome and cardiovascular disease. Hence this tool may be useful for motivating people for primary prevention of diabetes, metabolic syndrome and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of course many studies were done in India validating the IDRS score done by Anandh Vardhan et al among medical students, Lanord Stanley JM et al study among rural community in Tamil Nadu, Adhikari P et al among South Indian population. [7][8][9] All these validation studies accepts that the MDRF -IDRS predicts diabetes but also identified those with metabolic syndrome and cardiovascular disease. Hence this tool may be useful for motivating people for primary prevention of diabetes, metabolic syndrome and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Similarly in a separate study by Anand et al found 40% to be in moderate to high risk group. 22 Study done by Nagalingam S et al found 37.5% and 44.7% students in high and moderate risk group respectively. 23 Another study in Karnataka found 86% students in moderate to high risk group.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies proportion of abnormal WC ranges from 8.6-59.9%. [20][21][22][23][24][25] Except one study, all other studies reported high proportion, around half of students with abnormal WC. 22 Central obesity specially is a known important risk factor for cardio-metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations